ANALISIS STRATEGI PEMASARAN DIGITAL TOKOPEDIA DAN SHOPEE TERHADAP LOYALITAS PELANGGAN E-COMMERCE - Anggit Dyah Kusumastuti; Ahmad Agus Eko Tri Wahyudi; Tezhalonika Marchela; Luluk Nur Aulia; Maharani Aura Budi Lestari; Greysha Maretta Zahralia Aurel (Fakultas Ekonomi dan Bisnis, Universitas Wiraraja Madura, 2025)
The rapid development of digital technology has brought about significant changes in the business world, particularly in the e-commerce sector. The ease of internet access and the use of smartphones have simplified buying and selling activities, which can now be done efficiently through online applications. In recent years, Tokopedia and Shopee have become the two major players dominating the Indonesian market and competing fiercely to retain customer loyalty. The integration of platforms like TikTok Shop with Tokopedia in 2024 presents increasing challenges for Tokopedia in building consumer trust after facing several regulatory hurdles. This research aims to analyse the digital marketing strategies implemented by Tokopedia and Shopee in increasing customer loyalty. Through a comparative approach and qualitative analysis, this study found that the effective use of social media, personalisation, and content marketing plays a key role in shaping positive perceptions and strengthening customer loyalty.